Kontrol terhadap Tubuh Perempuan pada Praktik Rejuvenasi Vagina - Angela Frenzia Frenzia (Universitas Gadjah Mada, 2020)
Vaginal rejuvenation has become a tradition among Indonesian women. The vaginal rejuvenation tradition was discovered in the Javanese kingdom era through traditional methods using vaginal evaporation and herbs. This tradition extends since the herbal medicine to dry and tighten the vagina, produced by the factory, and distributed to various regions in Indonesia. Traditional vaginal rejuvenation is still in demand and is carried out by Indonesian women to this day. Teenage women to married women consume traditional herbal vaginal seals. Many married women who choose to use a solid concoction “Tongkat Madura”, so it is faster to get the results of a dry and tight vagina. As the evolvement of medical technology, recently it is known well a treat to reconstruct the vagina by using laser technology or surgery which is called as vaginal rejuvenation. The woman who does this kind of treatment usually because they want to have an “ideal” vagina for the sake of harmonies sexual relations. The idea of this “dry and tight” vagina comes from generation to generation where every woman in Indonesia is thought to take treat their vagina carefully so that she can satisfy her sex partner. Derive from Foucault’s idea of political body technology and some ideas from feminists, this research is aimed to examine the inequity experienced by women in the practice of vaginal rejuvenation in Indonesia. This research is exploratory. The analysis was performed on the data in the form of observations and interviews. This research found inequities experienced by women in the form of objectification of the female body; women’s subordination; women suffer in the process of reconstruction of their bodies to fulfill men’s pleasures and rules in society.Keywords: Control toward Women; Gender; Patriarchal Constructions; Sexuality; Vaginal Rejuvenation.